Cellulose polymorphs and physical properties of cotton fabrics processed with commercial textile mills for mercerization and liquid ammonia treatments*. Issue 16 (October 2014) - Kafle, Kabindra; Greeson, Kenneth; Lee, Christopher; Kim, Seong H
We report the detection of cellulose polymorphs, using spectroscopic and diffraction techniques, in cotton fabrics treated with commercial textile mill processes designed for better dyeing and mechanical properties. Vibrational sum frequency generation (SFG) spectroscopy analysis of cotton is known to be selective and sensitive to the crystalline cellulose portion in the sample. The SFG analysis results were compared with the results from conventional analytical techniques such as X-ray diffraction (XRD) and infrared (IR) spectroscopy. The XRD detection of a small fraction of cellulose II present in the partially-mercerized fabric was difficult, while SFG and IR analysis indicated the partial conversion of cellulose I to II without significant reduction of the cellulose crystallinity. Processing the cotton fabric with the liquid-ammonia treatment mill caused partial conversion of cellulose I to III and significant reduction of the overall crystallinity of cellulose. All XRD, SFG, and IR techniques were able to monitor this conversion. When the cotton fabric was treated with the partial mercerization process first and then the liquid-ammonia process, both cellulose II and cellulose III were produced and identified with SFG. But XRD and IR failed to detect the presence of cellulose II in the mercerized and ammonia-treated fabric. The polymorphic changes found in the SFG, XRD, and IR analyses provided insights into the physical property changes of cotton fabric after commercial mercerization and liquid-ammonia treatment processes.